Histologic transformation to small-cell lung cancer following gefitinib and radiotherapy in a patient with pulmonary adenocarcinoma. Issue 6 (December 2019) - Fiore, Michele; Trecca, Pasquale; Perrone, Giuseppe; Amato, Michelina; Righi, Daniela; Trodella, Lucio; D'Angelillo, Rolando M.; Ramella, Sara
Introduction: Targeted therapies against epidermal growth factor receptor (EGFR) have revolutionized the treatment of a subset of lung adenocarcinomas that have EGFR-activating mutations; however, all patients treated with EGFR tyrosine kinase inhibitors (TKIs) ultimately develop resistance. Histologic transformation of EGFR-mutant adenocarcinoma to small cell lung cancer (SCLC) is a resistance mechanism rarely reported in the literature. Case presentation: We describe the case of a woman with metastatic lung cancer adenocarcinoma with mutated EGFR with an initial response to gefitinib and radiation therapy, who progressed after 18 months due to the development of a resistance mechanism. The new biopsy performed after progression highlighted histologic transformation to SCLC, while maintaining the original EGFR mutation. Conclusions: To better identify patients who progress after TKIs and radiation therapy, it is important to perform tumor rebiopsy and collect data to study mechanisms of acquired EGFR TKI resistance.